Fluorometric determination of free glucose and glucose 6-phosphate in cows' milk and other opaque matrices. (1st January 2015) - Larsen, Torben
Highlights: New analytical method for determination of free glucose and glucose 6-phosphate in milk. Standards are based on milk stripped of intrinsic glucose and glucose 6-phosphate. The assays operate directly on full milk without pre-treatment of the sample. Automated assays permit "high output" capacity of analyses. Ordinary cow's milk contain 140–530 μM free glucose and 10–220 μM glucose 6-P ( n  = 1637). Abstract: Analyses of free glucose and glucose 6-phosphate in milk have until now been dependent upon several time consuming and troublesome procedures. This has limited investigations in the area. The present article presents a new, reliable, analytical procedure, based on enzymatic degradation and fluorometric detection. Standards and control materials were based on milk that was stripped of intrinsic glucose and glucose 6-phosphate in order to obtain standards and samples based on the same matrix. The analysis works without pre-treatment of the samples, e.g. without centrifugation and precipitation of protein with acids.